Penyuluhan dan Praktik Larvasida Nabati Sebagai Upaya Penurunan Penyakit Demam Berdarah Dengue (DBD) - Leony Prianka Devina; Mokhammad Najib Prastiyo; Alva Saputra; Zulfa Syauqiah; Akhmad Khisabil Islam; Vanissa Aviana Melinda (JRCE (Journal of Research on Community Engagement), 2026)
Dengue Hemorrhagic Fever (DHF) in Indonesia is still a health problem caused by the Dengue virus through the bite of the Aedes aegypti mosquito. The use of synthetic pesticides is often used to control mosquitoes. Synthetic pesticides as drugs that are effective, practical, powerful, and affordable make why synthetic pesticides more widely used. Even though the continuous use of synthetic pesticides can cause nuisance pests or larvae to become resistant to pesticides. In its eradication, the use of insecticides has proven to have many negative impacts. However, the use of vegetable insecticides is considered more environmentally friendly and natural. The purpose of this study was to find out the practice of making and applying vegetable larvicide in Kucur Village, Dau District, Malang Regency. The research method used is CBR (Community Based Research). CBR is a research model that includes the community as a partner. The application of CBR aims to answer the problems currently being faced by the community by offering a solution and contributing to the solution. These observations and surveys were carried out independently by service members from village areas, fields, and tourist attractions. The results of the research included how to make vegetable larvicide from lemongrass leaves, how the larvicide works, and the use of vegetable larvicide in the given object. The conclusion of this study was that the community enthusiastically welcomed and participated in enlivening the "Extension and Practice of Vegetable Larvicides as an Effort to Reduce Dengue Hemorrhagic Fever"